Modern trends of development of economic Analysis Methods - N. S. Plaskova; Е. V. Prokofieva (Учёт. Анализ. Аудит)
The focus of this paper is on the improvement issues of the theoretical foundations of economic analysis, on the development of its instrumental framework and practical use of economic and mathematical methods in the study of the costs of industrial organizations. One of the main directions of creating an effective management system for industrial organizations is the formation of a high-quality information and analytical base, of which the methodological basis for the analysis should be improved in terms of using the whole set of classical and new methods of economic-mathematical toolkit. On the basis of its classical methodological toolkit, the development of the scientific foundations of economic analysis should be enriched by modern methods, types, and directions of the studies of economic processes and their results at all levels of management. The intensification of the search for the new opportunities of the existing tools of economic analysis and the emergence of fundamentally new methods in its arsenal is determined by their practical relevance. The article attempts to adapt the classical correlation economic-mathematical method of analysis and use it to solve the practical management task of ranking cost items to form an objective view of the impact of their nature and structure on the levels of assortment margin and full profitability of a production organization. The mechanism of using the correlation-regression method of economic analysis offered in the article is sufficiently versatile and for the necessary management purposes it allows ranking the costs associated with the production and sale of products, to form objective information about the structure and levels of variable and fixed costs in the retrospective and predictive aspects that gives the opportunity to assess the aggregated and detailed indicators of marginal profitability of the organization realistically as a whole and for various objects of calculation.